Rancangan Desain Sistem Monitoring Home Quarantine Kasus Konfirmasi Tanpa Gejala Covid-19 Berbasis Web-Mobile Di Surabaya - Hamidah Indrihapsari; Sabarinah Prasetyo; Kemal Nazaruddin Siregar (Preventia : The Indonesian Journal of Public Health, 2021)
As a new emerging and highly infectious disease, the cases of Coronavirus Disease (COVID-2019) have been growing rapidly. To curb the spread of COVID-19, one of the measures is quarantining the patients who are infected in the hospital or in a dedicated monitoring center. However, because of the fast spread of the coronavirus, the health resources such as health facilities, healthcare workers, and monitoring centers, are overwhelmed. To handle this problem, asymptomatic patients are suggested to self-quarantine in their own home. However, this can be challenging because it is hard to monitor these patients all the time. Global Positioning System (GPS) & Geofencing technology can become solution for this issue, to monitor the COVID-19 patients by tracking the location of these home-quarantined patients. Web-mobile application for monitoring COVID-19 home-quarantined patients is proposed to handle the problems arising because of COVID-19. The prototyping method is used in this system development until step 2; 1) system requirement analysis, and 2) system design. System requirement analysis was done with qualitative method via online in-depth interviews with 5 (five) potential users (a staff from District Health Office of Surabaya, one from Primary Healthcare Centers in Surabaya, one surveillance staff, one doctor, and one asymptomatic COVID-19 patient from Surabaya) and literature review. System design consists of logic designs and interface designs which is designed to fulfill the requirements needed in the first step. Most of the potential users interviewed, stated that the development of this system will be really helpful for them, but it must be followed with the local regulation about the consequences of breaking the home quarantine rule. In conclusion, this system design can be the basic concept for developing the system in the next step.